Bangla text extraction by digital image processing - Hoque, A. K. M Rashedul; Pandit, Proma Mrittika; Nasreen, Najia; Raihan, Hasin (2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.